Willingness to uptake breast cancer screening among rural women in Southwestern Nigeria (2017)
Background: The mortality attributed to breast cancer remains high especially among rural dwelling women in low-income countries. Late diagnosis that may be as a result of poor knowledge and nonutilization of available screening has been implicated in the high mortality burden. Enhancing access to and uptake of breast cancer screening will reduce the cancer burden. Objectives: This study was conducted to assess the willingness to uptake breast cancer screening among rural women in South Western Nigeria. Factors associated with willingness to uptake breast cancer screening were also determined. Methods: A community-based cross-sectional design using multi-stage sampling was used to select 920 women in Igbo-Ora, South Western Nigeria. An interviewer-administered questionnaire was used for data collection. Data was analysed using SPSS at a 5% level of statistical significance. Results: The respondents were aged 15 to 86 years with 795 (86.4%) being within the reproductive age group. Of total respondents, 546 were aware of breast cancer of which 171 (31.3%) had good knowledge about the symptoms of breast cancer. Of the 834 respondents who had never screened for breast cancer, 651 (78.1%) were willing to screen. Respondents within the reproductive age group and those that knew someone with breast cancer had odds of 2.7 and 2.5 respectively of being willing to uptake breast cancer screening. (OR=2.9; 95% CI=1.8-5.1 and OR=2.5; 95% CI 1.2-5.7) Conclusion: Although the knowledge of breast cancer and the awareness of screening methods among women in rural area is low, their willingness to get screened remains high. The use of survivors as well as survivor relatives should be considered during community-based health programmes aimed at improving uptake of screening among this population.